Molecular dynamics simulation and experimental study into effect of temperature on hardness of ice abrasives - Li, Zhiping; Liu, Yong; Wei, Jianping; Wu, Jiaojiao (Frontiers in Earth Science, 2023)
Ice abrasive jet technology is a green and environmentally friendly process with wide application prospects in the field of surface treatment. Ice abrasive jets constitute an essential technical parameter of the process, and temperature affects the hardness of ice. Therefore, in this paper, we investigated the hardness of ice at different temperatures. The dynamic characteristics of ice at different temperatures were simulated using molecular dynamics methods, and the laws of the dynamic characteristics of ice with temperature were analysed. Hardness testing experiments were carried out to grade the hardness of ice and then linearly fitted the hardness versus temperature. The results show that as the temperature increased, the dynamic characteristics of ice changed correspondingly, and the intermolecular hydrogen bonds and van der Waals interactions of ice weakened. From a chemical perspective, with the increase in temperature the intermolecular force weakens, the lattice energy of the crystal decreases, the resistance required to destroy the crystal decreases, and the crystal exhibits low hardness. Temperature affects the hardness of ice by changing the strength of the intermolecular force. The experimentally measured ice hardness was classified into five classes, and the fit revealed a strong linear correlation between ice hardness and temperature. In this study, numerical simulations were performed and experimental results were analyzed to identify the effect of temperature on the hardness of ice by changing the force between ice molecules, which is crucial for improving the erosion efficiency of ice abrasive jets.